Altered Collection Interfaces in Hematopoietic Progenitor Collection of Sickle Cell Patients. (11th September 2019) - Tsai, Jonathan; Manis, John; Ching, Kimberly
Abstract: Sickle cell disease (SCD) results from a point mutation in the beta globin gene leading to abnormal hemoglobin production and, correspondingly, abnormal sickling of erythrocytes that result in chronic anemia and vaso-occlusive crises. Patients with sickle cell are commonly treated with lifelong transfusions or hydroxyurea to increase fetal hemoglobin to ameliorate sickling. Evolving therapies are aimed at correcting known mutations with gene therapy on autologous hematopoietic stem and progenitor cells (HSCs), indicating a growing need for optimal stem cell collections from SCD patients. Recent studies have shown the safety and efficacy of plerixafor to increase peripheral CD34+ cells, enhancing collection. Here we show that standard apheresis collection procedures from sickle cell patients are inefficient when compared to healthy donors. Eleven patients with SCD were recruited to receive plerixafor and followed by peripheral CD34+ cell monitoring and apheresis collection. Overall, efficiency ranged from 2% to 55% with no correlation to total peripheral CD34+ cell count. To better understand where the CD34+ cells sedimented in the apheresis instrument, we collected different layers of the interface ranging from 3% to 10% estimated Hct and found that deeper layers with higher hematocrit (7.5%-10%) are enriched for CD34+ cells when compared to historical donors with healthy red cells. All patients had undergone red cell exchange prior to collection, yet this intervention did not prevent the altered sedimentation of CD34+ cells. These findings indicate that CD34+ cells from SCD patients sediment at a deeper, higher Hct interface layer during apheresis and support the altered collection practices for the efficient collection of HSCs for cellular therapies.